PENGARUH KUALITAS PELAYANAN DAN KEWAJARAN TARIF TERHADAP NILAI KONSUMEN SERTA RETENSI PELANGGAN UNTUK PENERBANGAN DOMESTIK NIAGA FULL SERVICES DI INDONESIA - Soelasih, Yasintha (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2014)
Competition in the airline industry is very high. This can be seen that there are so many enterprises in this industry. There is a change in the legacy carriers to low cost carriers. Companies that still maintain the legacy carriers will have an impact on higher rates charged to passengers compared to the low cost carriers. Therefore the companies that use the legacy carriers should be able to provide better services than the companies that use low cost carriers. The companies should pay attention to service quality and fairness of tariffs, so that consumers perceived value to these companies are much more higher than to the company that using low cost carriers. As a result, customer retention occurs.